English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^2+2x
=====
x^2+x-2

2006-12-07 12:56:48 · 5 answers · asked by odie_109 1 in Science & Mathematics Mathematics

5 answers

x^2+2x=x(x+2)

bottom has 2 roots:

x=(-1 +/ sqrt(1+4*2) ) / 2
i.e. x=-2 and x=1

so bottom is (x+2)(x-1)

and fraction reduces to:

x/(x-1)

2006-12-07 13:00:36 · answer #1 · answered by Anonymous · 0 0

first simplify each part:

x^2 + 2x = x(x+2)
x^2 + x - 2 = x^2 + 2x - x - 2 = x(x+2) - (x+2) = (x+2)(x-1)

now put it altogether:

x(x+2)
over
(x+2)(x-1)

You can notice that (x+2) in both expressions cancel each other, which leaves you with
x
over
(x-1) as a result.

Note:
- In this case we cannot perform usual checkup of the solution.
- should this be an equation problem, some extended rules would apply (won't go any further here, just to bring it to your attention)

2006-12-07 21:13:00 · answer #2 · answered by Mirta G 2 · 0 0

x ( x + 2 )
===========
( x + 2 ) ( x + 1 )

The ( x + 2 ) 's cancel out. So you are left with:

x
====
x + 1

2006-12-07 21:03:48 · answer #3 · answered by Woodie W 1 · 0 0

x(x+2)÷(x+2)(x-1)

cancel the (x-2) in the top and the bottom
so you have x ÷ (x-1)

2006-12-07 21:01:33 · answer #4 · answered by che_karlos 2 · 0 0

It cant't be simplified anymore than it already is

2006-12-07 21:00:17 · answer #5 · answered by Jas2Love9210 2 · 0 0

fedest.com, questions and answers